Clinical and Genetic Heterogeneity in a Cohort of Chinese Children With Dopa-Responsive Dystonia - Chen, Yan; Bao, Xinhua; Wen, Yongxin; Wang, Jiaping; Zhang, Qingping; Yan, Jiayou (Frontiers in Pediatrics, 2020)
Background: The aim of this study was to investigate the genetic and clinical features of dopa-responsive dystonia (DRD) in China. Method: Characteristics of gene mutations and clinical manifestations of 31 patients diagnosed with DRD were analyzed retrospectively. Result: From January 2000 to January 2019, 31 patients were diagnosed with DRD. Twenty (64.5%) were male, and 11 (35.5%) were female. Ten patients (32.3%) had classic DRD, 19 (61.3%) had DRD-plus, and 2 (6.4%) patients had mutations in the dopamine synthetic pathway (PTS gene mutation) without a typical phenotype (not DRD or DRD-plus). Twenty-eight (90.3%) patients underwent genetic testing. Homozygous or compound heterozygous TH gene mutations were found in 22 patients. GCH1 and PTS gene mutations were found in 2 patients. Heterozygous TH mutation and genetic testing were negative in 1 patient. They took different doses of L-dopa, ranging from 0.4 to 8.7 mg/kg/d. Patients with classic DRD responded well. In patients with DRD-plus, 94.7% (18/19) responded well with residual symptoms. One patient (5.3%) did not show any improvement. Conclusion: DRD can be divided into classic DRD and DRD-plus. In this cohort, the most common pathogenic gene was TH. Fever was the important inducing factor of the disease. L-dopa has sustained and stable effects on patients with classic DRD. In patients with DRD-plus, treatment with L-dopa could ameliorate most of the symptoms.